A facile construction of gradient micro-patterned OCP coatings on medical titanium for high throughput evaluation of biocompatibility. Issue 22 (19th May 2016) - Song, Ran; Liang, Jianhe; Lin, Longxiang; Zhang, Yanmei; Yang, Yun; Lin, Changjian
Abstract : A facile construction of gradient micro-patterned octacalcium phosphate (OCP) coatings on titanium was developed for high-throughput screening of biocompatibility and bioactivity. Abstract : Base on a superhydrophobic–superhydrophilic micro-patterned template, a facile construction of gradient micro-patterned octacalcium phosphate (OCP) coatings on titanium has been firstly developed for high-throughput evaluation of biocompatibility. The gradient OCP coatings with tunable crystal morphologies involving scattered-flower-like, scattered-flower-ribbon-like, short-ribbon-like and long-ribbon-like were fabricated in different micro-units on the same surface. The significant difference of mineralization behavior of the gradient OCP coatings in the micro-patterns was observed visually and efficiently. In vitro cultures of MC3T3-E1 cells showed that the number and morphology of cells selectively adhered on the micro-units of gradient structure of OCP coatings were distinctly different, indicating that the cells are sensitive to the different structures of OCP coatings on medical titanium. The gradient micro-patterned construction is potentially a powerful method for not only high-throughput screening of the biocompatibility of various biomaterials, but also efficient development of advanced biomaterials by controlling cell immobilization and inducing cell response.